2010
DOI: 10.1002/path.2762
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of LMO4 induces centrosome amplification and mitotic spindle abnormalities in breast cancer cells

Abstract: The LIM-only protein, LMO4, is a transcriptional modulator overexpressed in breast cancer. It is oncogenic in murine mammary epithelium and required for G2/M progression of ErbB2-dependent cells as well as growth and invasion of other breast cancer cell types. However, the mechanisms underlying the oncogenic activity of LMO4 remain unclear. Herein, we show that LMO4 is expressed in all breast cancer subtypes examined and its expression level correlates with the degree of proliferation of such tumors. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
(85 reference statements)
0
15
0
2
Order By: Relevance
“…LIM domain only 4 (LMO4) expression is frequently elevated in breast cancer (34). Additional experiments in breast cancer cells from various subtypes demonstrated that LMO4 induced cyclin D1 and cyclin E1 expression to promote cell cycle progression and facilitate cell proliferation (35). The expression of LMO4 was regulated by miR-409-3p in colorectal cancer (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIM domain only 4 (LMO4) expression is frequently elevated in breast cancer (34). Additional experiments in breast cancer cells from various subtypes demonstrated that LMO4 induced cyclin D1 and cyclin E1 expression to promote cell cycle progression and facilitate cell proliferation (35). The expression of LMO4 was regulated by miR-409-3p in colorectal cancer (50).…”
Section: Discussionmentioning
confidence: 99%
“…6A). LMO4 is a transcription factor that activates cyclin D1 and E1 transcription and mediates cell cycle progression (35). Knockdown of SNHG1 reduced cyclin D1 and cyclin E1 mRNA levels (Fig.…”
Section: Snhg1 Knockdown Downregulates Lmo4 Expression and The Expresmentioning
confidence: 99%
“…It has been reported that LMO4 plays a crucial role in the centrosome cycle as well as cell cycle progression in breast cancer cells. It can regulate several cell cycle-related genes, including cyclin D1, cyclin E, p21, p27 and BRCA1 (11,18). Strikingly, growing evidence indicates that LMO4 can modulate progression of breast cancer cell cycle by indirectly enhancing the expression of G 1 cyclins, such as cyclin D1 and cyclin E, and contributes to the growth of multiple breast cancer cells (1921).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that LMO4 is a downstream target of ERBB-2 and its signaling protein PI3K and is essential for ERBB2-mediated proliferation and cell cycle progression in ERBB-2-dependent breast cancer cells (Montañez-Wiscovich et al, 2009). Pathological results also showed that the aberrant expression of LMO4 on the centrosome cycle promoted LMO4-induced breast cancer formation (Montañez-Wiscovich et al, 2010). Increasing evidence suggested that the LIM domain of LMO4 protein acted as a docking site for the assembly of multiprotein complexes including HEN1 (Manetopoulos et al, 2003), CtBP-interacting protein and BRCA1 complex (Sum et al, 2002), ERα and MTA1 complex (Singh et al, 2005), Clim-2/ldb-1/Nl1 (Sugihara et al, 1998), DEAF1 (Hahm et al, 2004), peroxisome proliferation-activated receptor-γ (PPARγ) (Schock et al, 2008), cAMP response element-binding protein (CREB) complex (Kashani et al, 2006), glycoprotein 130 complex (Novotny-Diermayr et al, 2005), and transcription modulator Cited2 (Michell et al, 2010), which provided further compelling evidence for LMO4 playing a significant role in cells.…”
Section: Discussionmentioning
confidence: 97%